Marilog-Arakan Land Reservation strategic plan - Paraba, Rene S. (School of Management, University of the Philippines Mindanao, 2007)
Marilog-Arakan Land Reservation (MALR) is a treasure lying bare, untapped and disclosed. This study hunts for this hidden treasure. It starts by scanning thoroughly the veracity of information. Slowly MALR unfolds its deep secrets by leaving traces of luster in every trail until everyone is captured, amazed and in-loved. The internal and external environment may look bleak. The initial interventions seemed chaotic. And the collaborative alliances resemble a distorted orchestra. Putting every piece together to form the jigsaw puzzle, something significant is being revealed. All of them points to an area marked ?X? and disclosed the hidden potentials of MALR. MALR is an indivisible whole and a home to the three capitals that shape-up life support system, the natural capital, social capital and the economic capital. With right packaging, MALR can be the convergence nucleus for commitment and participation of development institutions- it is a model for sustainable development in capsule. Disclosing this treasure for public support and partnership ensures MALR sustainability. However, it has to overcome the stumbling block that can cause sudden death and end its noble aspirations-this is the approval of the UP Board of Regents regarding MALR independent or autonomous operation as special project/program of UP Mindanao. It takes a persuasive leadership and technical prowess to clear this matter to the BOR. But, the challenge is worth enduring for the prize is a valuable contribution to global ecosystem and planetary ethics. This strategic plan therefore, put together the potentials and competitive advantages of MALR as the heart of its existence and unambiguous direction. Purposely, this is to bring MALR at the portals of UP culture of excellence. Though the study is faced with limitations and constraints especially in the availability of validated data, the writer believes that what is at hand is sufficient to craft the strategic direction of MALR. The study then proceeded in this assumption and discovers the nitty-gritty of institutional and legal impediments that hinders the growth of MALR. This plan therefore, uses these challenges as springboard for MALR take-off. The strategic directions unearthed from inherent and implied aspirations of MALR?s stakeholders are captured in the Vision, Mission, Goal and Objectives that guarantees optimal impact for the next five (5) years. The strategic or drivers of these directions are promising interactive encounter for empowerment not only to beneficiaries but most of all for MALR and implementers as well. This embedded symbiotic relationship is indeed the sustainable development everyone is aspiring for. The objective of the study is simply finding a possible positioning for MALR to be a worthy project to explore on. But, Marilog-Arakan Land Reservation unravels its might and true worth-it is? life in itself. Marilog-Arakan Land Reservation (MALR) is a treasure lying bare, untapped and disclosed. This study hunts for this hidden treasure. It starts by scanning thoroughly the veracity of information. Slowly MALR unfolds its deep secrets by leaving traces of luster in every trail until everyone is captured, amazed and in-loved. The internal and external environment may look bleak. The initial interventions seemed chaotic. And the collaborative alliances resemble a distorted orchestra. Putting every piece together to form the jigsaw puzzle, something significant is being revealed. All of them points to an area marked ?X? and disclosed the hidden potentials of MALR. MALR is an indivisible whole and a home to the three capitals that shape-up life support system, the natural capital, social capital and the economic capital. With right packaging, MALR can be the convergence nucleus for commitment and participation of development institutions- it is a model for sustainable development in capsule. Disclosing this treasure for public support and partnership ensures MALR sustainability. However, it has to overcome the stumbling block that can cause sudden death and end its noble aspirations-this is the approval of the UP Board of Regents regarding MALR independent or autonomous operation as special project/program of UP Mindanao. It takes a persuasive leadership and technical prowess to clear this matter to the BOR. But, the challenge is worth enduring for the prize is a valuable contribution to global ecosystem and planetary ethics. This strategic plan therefore, put together the potentials and competitive advantages of MALR as the heart of its existence and unambiguous direction. Purposely, this is to bring MALR at the portals of UP culture of excellence. Though the study is faced with limitations and constraints especially in the availability of validated data, the writer believes that what is at hand is sufficient to craft the strategic direction of MALR. The study then proceeded in this assumption and discovers the nitty-gritty of institutional and legal impediments that hinders the growth of MALR. This plan therefore, uses these challenges as springboard for MALR take-off. The strategic directions unearthed from inherent and implied aspirations of MALR?s stakeholders are captured in the Vision, Mission, Goal and Objectives that guarantees optimal impact for the next five (5) years. The strategic or drivers of these directions are promising interactive encounter for empowerment not only to beneficiaries but most of all for MALR and implementers as well. This embedded symbiotic relationship is indeed the sustainable development everyone is aspiring for. The objective of the study is simply finding a possible positioning for MALR to be a worthy project to explore on. But, Marilog-Arakan Land Reservation unravels its might and true worth-it is...life in itself.